Design of an inclusive & interactive educational textile toy - Pereira, Cleber Augusto (2017)
The market for educational toys is scarce in products specifically developed for blind and low sighted children, aiming not only at their motor and cognitive development as well as to the non-stigmatization of these children. Considering the development of educational toys, and based in previous research work [1], we found that textile materials offer an enormous application capability in this regard due not only to their flexibility in use and maintenance of properties, but also because of our familiarity with these materials.The main goal of this project is the study of the emotional response to an interactive educational textile toy by children with visual impairments - blind or partially sighted. In this way the project is based on four main axes: knowing the user, identifying his specific needs; knowing the product-user relationship with a special focus on tactile and emotional perception; study textile structures to best fit the design; and, finally, evaluate the user's response to the developed product by evaluating the product experience.